Autoimmune hepatitis/primary sclerosing cholangitis overlap syndrome in a child: Diagnostic usefulness of magnetic resonance cholangiopancreatography - Lee, Way Seah; Saw, C.B.; Sarji, S.A. (Wiley, 2005)
A 5-year-old Chinese girl with 1-year history of progressive jaundice, steatorrhoea and pruritus was referred. Physical examination showed failure to thrive, marked jaundice, finger clubbing and hepatomegaly. There was laboratory evidence of cholestatic jaundice and autoimmunity, with marked elevation of alkaline phosphatase (ALP) and gamma-glutamyl transferase (gamma GT). Histology of percutaneous liver biopsy revealed hepatitis around the portal triad, as well as features of liver cirrhosis. Primary sclerosing cholangitis (PSC) overlapping with autoimmune hepatitis (AIH) was suspected. Endoscopic retrograde cholangiopancreatography (ERCP) was not feasible as there was no weight-appropriate ERCP scope available. Magnetic resonance cholangiopancreatography (MRCP) was performed and revealed areas of irregularity and slight attenuation of the right and left hepatic ducts, representing stricturing, in keeping with PSC. PSC/AIH overlap syndrome was diagnosed in this child in which MRCP has contributed to its diagnosis.